Effect of dietary chlorella vulgaris on liver enzymatic profiles of rohu Labeo rohita (Hamilton, 1822) - Pradhan, Jyotirmayee; Das, Basanta Kumar (Indian Journal of Fisheries, 2015)
Labeo rohita fingerlings (25 Â± 2 g) were fed on diets supplemented with Chlorella vulgaris powder at the rate of 0, 0.1, 0.5 and 1.0 g kg-1 for a period of 90 days. Blood and serum samples were collected at 30 days interval and assayed for enzymatic parameters viz., serum aspartate aminotransferase (AST), serum alanine aminotransferase (ALT) and alkaline phosphatase (ALP). After 90 days feeding fish were challenged with a pathogenic strain of Aeromonas hydrophila and mortalities were recorded over 10 days post-challenge. Serum AST and ALT activity were significantly (pâ‰¤0.05) different in all the treated groups of fish on day 30 and on day 10 bacterial post-challenge as compared to control. The highest survival on 10th day post-challenge (86.5%) was recorded in group fed with 0.1% Chlorella supplemented diets.The intake of C. vulgaris at different dosages altered the AST, ALT and ALP activity, but the variation was within the normal ranges that did not hamper the growth of fish. The study indicated that dietary supplementation of C. vulgaris did not negatively affect liver function, and was found to have growth promoting activity in rohu.